Evaluation of adherence and clinical outcomes in patients undergoing allogeneic haematopoietic stem cell transplantation - Lorena García-Basas (Farmacia Hospitalaria, 2020)
Objective: To measure adherence to cyclosporine, tacrolimus and sirolimus prophylaxis against secondary graft failure; cyclosporine, tacrolimus, sirolimus and mycophenolate prophylaxis against graft-versus-host disease; and posaconazole, voriconazole, valganciclovir prophylaxis against infection in patients undergo to transplantation of haematopoietic stem cells; and to analise the incidence of acute complications based on adherence.Method: Retrospective observational study of patients who underwent allogeneic haematopoietic stem cell transplantation between May 2017 and May 2018. Analyses were carried out between 0 and +100 days post-engraftment. Whenever possible, adherence to mycophenolate, tacrolimus, sirolimus, posaconazole, voriconazole and valganciclovir was evaluated by means of the dispensation records of the Pharmacy Department of our hospital. To be considered adherent, patients should have proved an adherence rate equal to or higher than 95%. Adherence to cyclosporine was determined based on serum levels. Patients were considered to be non-adherent if their cyclosporine serum concentrations dropped below 100 ng/mL at any time between days 0 and +100, in the absence of any specific justifying circumstances. The association between adherence and the inci dence of acute complications (secondary graft failure, acute graft-versus-host disease and infection) was determined by means of the odds ratio (confidence interval: 95%).Results: The study sample was made up by 46 patients, all of whom were started on immunosuppressive cyclosporine prophylaxis; 8.7% needed to be switched to tacrolimus or sirolimus due to toxicity issues. All the patients received cyclosporine as prophylaxis against graft-versus-host disease. Mycophenolate was also administered in 41.3% of cases. A total of 82.6% patients were found to be adherent to their prophylaxis treatment against graft failure and 80.4% were found to be adherent to prophylaxis against graft-versus-host disease. All patients were adherent to anti-infection prophylaxis. The incidence of acute graft-versus-host disease in prophylaxis-adherent patients was 45.9%, compared with 55.6% for non-adherent patients (odds ratio 0.68; confidence interval: 95% 0.157-2.943; p = 0.718). Conclusions: Patients undergoing allogeneic haematopoietic stem cell transplantation demonstrated acceptable adherence to prophylaxis against acute complications, although a considerable percentage of patients was found not to take their medication as prescribed. Correct adherence to immunosuppressants seems to reduce the risk of developing acute graft-versus-host disease.